Strategies on resort areas and their lifecycle stages - Andriotis, Konstantinos (My University, 2001)
In the business level there are many empirical studies suggesting various market/product strategic options. There are also four stages of product lifecycle (introduction, growth, maturity and decline). The pattern of the product lifecycle can be utilised as a framework for examining the changing environment of a destination in relation to the expansion of tourism. Stages of destination development include: exploration, involvement, development, maturity and decline or rejuvenation. The specific features of each stage of a destination's lifecycle call for different strategies. Bearing this in mind, it is the aim of this pa-per to examine the usefulness of strategies risen in the business field for resort areas and their lifecycle stages.
Keywords: Resort lifecycle; Strategic options